STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN CITRA MADRASAH DI MTs MA’ARIF NU KALIGIRI KECAMATAN SIRAMPOG KABUPATEN BREBES - Nisa, Elnisa (STIT Pemalang, 2022)
This study aims to determine the strategy of the head of madrasah in improving the image of the madrasah in Madrasah Tsanawiyah Ma'arif Nahdhatul Ulama 'Kaligiri, Sirampog District, Brebes Regency. In addition to knowing the strategy of the head of madrasah in improving the image, he also knows the implications of implementing the strategy by the head of madrasah which has an impact on improving the quality of madrasah academics. This type of research is qualitative research. In completing this research, the researcher collected data in the form of interview manuscripts, observations, field documentation, and other supporting official documents. So that a complete picture can be obtained of the research conducted by researchers. The results of this study illustrate that the image of Madrasah Tsanawiyah Ma'arif Nahdhatul Ulama 'Kaligiri, Sirampog District, Brebes Regency can be categorized as good. This is indicated by the increasing public trust in the Madrasah with the increasing number of students. The strategy of the head of madrasah in improving the image of the madrasah is by carrying out internal improvements through increasing the competence of teachers and education personnel, collaborating with related parties, arranging administrative systems and governance and conducting intense promotions to the community. The implications of the madrasah principal's strategy in improving the image can be seen from the increase in academic and non-academic achievement